Pengaruh Digitalisasi Pajak dan Kesadaran Wajib Pajak Terhadap Kepatuhan Pelaporan Wajib Pajak Orang Pribadi di KPP Pratama Kota Solok - Rezi Yulia Pratiwi; Rani Sofya (Universitas Negeri Padang, 2023)
Technological advances make electronic systems applied to the field of taxation to provide convenience to taxpayers in carrying out their obligations, technological advances present a modern administrative system called digitalization. The results of this research were analyzing impact of tax digitisation and awareness among taxpayers of compliance with the reporting of private taxpayers in KPP Pratama Kota Solok. This is a quantitative study that use association approaches. Data retrieval technique in the form of questionnaires. This study uses an accidental sampling strategy using a sample. number of 94 respondents. The results of this research were analyzing is multiple retrogression analysis. The results of this study, it can be seen that: 1) The simultaneous digitization of taxes and taxpayer awareness have a significant impact on private taxpayer compliance with reporting on KPP Pratama Kota Solok. 2) The digitalization of taxes has had a positive and significant impact on private taxpayer compliance with KPP Pratama Kota Solok reporting, and 3) taxpayer awareness positively and significantly on compliance with personal taxpayer reporting on KPP Pratama Solok City. The contribution of Tax Digitization and Taxpayer Awareness of Compliance with Reporting of Private Taxpayers in KPP Pratama Kota Solok is 51%.